Desempenho escolar em uma escola no campo - contingentes do fracasso escolar - Freo, Gabriela Favero (2019)
The research has as main objective to analyze and discuss the school performance of the students of the final years of elementary school of the EMEF João Gonçalves Vieira in the period of 2010-2017. As a thematic concern I assume the analysis of school performance from the perspective of the failure of schooling in the final years of elementary school. School failure is understood as a category of analysis that culminates in disapproval / retention, abandonmentt / avoidance, or infrequency. The effort of theoretical systematization on the subject contributes to the understanding of the phenomenon through the notes described in the school documents. For theoretical reasons, I align myself to the perspective of Patto (1988), Angelucci et al., (2004), Mello (1995), Machado (1994), Souza, M. (1991), Souza, D. (1991), Kramer e Leite (1996), in order to understand the institutional manifestation of school failure. As a methodological option, I link to Systemic Thinking based on Vasconcellos (2010), Pellanda (2009) and Maturana (1997) and use as a methodological contribution to Cartography, based on the Kastrup (2007). Deleuze and Guattari (1995) notes. The production of data is performed from the observationand analysis of the end of the year and class journals of the last seven years with the purporose of identifying and monitoring the recidivism of this process. In this way, I deepen the understanding about school failure, trying to relate it to the educacional context of the school; identify the average of achievement in the curricular components; and finally, to recognize some contingents that influence the low school performace. To analyze the data, I usedthe authors Charlot (2000, 2005, 2013), Meirieu (1998, 2000), Perrenoud (2000), Bossa (2008) Fernández (2013), Moojen (2009) and Bridi Filho and Bridi (2016). Basead on the analyses of the data, the elements of substance, emotional security, manifestation of behavior, relationship with daily life and the word of work, limits of the language and relation with knowledge are considered as contingents of school failure.